Systematic Literature Review Method for Identifying Efficiency and Photovoltaic Technology as a Renewable Energy Innovation - Audia, Washilla; Yendri Sudiar, Nofi; Hamdi; Yulkifli; Nofriandi, Alwi (Journal of Climate Change Society, 2024)
Photovoltaics or solar cells are a device that can convert/convert solar energy into electrical energy. The use of photovoltaics as a renewable energy innovation is very necessary in developing photovoltaic technology and increasing the efficiency of the energy produced. The main electricity supply is PLN, which is not always continuous in its distribution due to the limited availability of fossil energy. This can result in disruption of human activities and productivity. The technology developed is organic and inorganic photovoltaic technology. Photovoltaic efficiency refers to the ability of solar panels to convert sunlight energy into electrical energy. Currently it is not known how much technology has been developed by photovoltaics and the efficiency that photovoltaics have produced. This research aims to identify developments in photovoltaic efficiency research and technology used in the world whose data was obtained from related journals in 2013-2022. There are 1,503 studies related to photovotaic efficiency. The method used in this research is the Systematic Literature Review (SLR) Method. The SLR method is used to identify, review, evaluate, and interpret all available research on a topic area of ​​interest, with specific relevant research questions. By using the SLR method, a systematic review and identification of journals can be carried out, with each process following predetermined steps or protocols. The research results show that the technology that is widely used in developing photovoltaic efficiency is organic photovoltaic technology and the highest efficiency that has been obtained is 38.9%.